New data on chrysophycean stomatocysts from the phytoplankton of the Angara River River (East Siberia, Russia) and its tributaries, including descriptions of five new morphotypes - Firsova, Alena D.; Bessudova, Anna Y.; Likhoshway, Yelena V. (Phytotaxa, 2025)
Scanning electron microscopy identified 47 stomatocyst morphotypes in the spring phytoplankton of the Angara River and its tributaries (Irkut, Kuda, Kitoy, Belaya, and Ida Rivers), with 5 morphotypes new for science. Most of the morphotypes are widespread. Among them, 28 have been previously recorded in Russian reservoirs, and 22 are characteristic of Lake Baikal, from which the Angara River originates.